Morphology and molecular identification of Eurytrema spp. worm in Aceh cattle, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hanafiah M, Helmi TZ, Sutriana A, Bahi M. 2021. Morphology and molecular identification of  Eurytrema spp. worm in Aceh cattle, Indonesia. Biodiversitas 22: 5654-5661. The objective of this research was to determine the species of Eurytrema spp. in Aceh cattle which were slaughtered in slaughterhouses located in Banda Aceh, Indonesia. Identification of Eurytrema spp worm species was performed by Semichon’s Carmine staining, SEM and molecular method. The result fromSemichon’s Carmine staining and SEM method showed that worms coded E2 and E3 were Eurytrema cladorchis indicated by clearly visible protruding cirrus while worms coded E1, E4 and E5 were E. pancreaticum indicated by the absence of protruding cirrus. Molecular characterization of Eurytrema spp.produced fragments of approximately 700 bp in length. The phylogenic tree showed that Eurytrema spp.from Aceh cattle consisted of  2 clades: clade 1 was E. pancreaticum, while clade 2 was E. cladorchis. DNA sequencing result showed that the similarity of worm samples coded 1, 4, and 5 were 98.90% similar to E.  pancreaticum (KJ767631.1 and KC535543.1), and 96. 33% similar to E. cladorchis (MN566134.5 and MN566140.1), whereas the worm samples coded 2 and 3 were 97.53% similar to E. pancreaticum (KY490000.1 until KY490004.1), and 97.55 % similar to E. cladorchis (MN566135.1 until MN566140.1). This research was able to identify E. pancreaticumand E. cladorchis in Aceh cattle slaughtered in Banda Aceh slaughter houses.